Concurrent evaluation of cytokines improves the accuracy of antibodies against Mycobacterium tuberculosis antigens in the diagnosis of active tuberculosis. (March 2022) - Jacobs, Ruschca; Awoniyi, Dolapo O.; Baumann, Ralf; Stanley, Kim; McAnda, Shirley; Kaempfer, Susanne; Malherbe, Stephanus T.; Singh, Mahavir; Walzl, Gerhard; Chegou, Novel N.; ,; Walzl, Gerhard; et al.
Abstract: Background: Antibodies against mycobacterial proteins are highly specific, but lack sensitivity, whereas cytokines have been shown to be sensitive but not very specific in the diagnosis of tuberculosis (TB). We assessed combinations between antibodies and cytokines for diagnosing TB. Methods: Immuoglubulin (Ig) A and IgM antibody titres against selected mycobacterial antigens including Apa, NarL, Rv3019c, PstS1, LAM, "Kit 1" (MTP64 and Tpx)", and "Kit 2" (MPT64, Tpx and 19 kDa) were evaluated by ELISA in plasma samples obtained from individuals under clinical suspicion for TB. Combinations between the antibody titres and previously published cytokine responses in the same participants were assessed for diagnosing active TB. Results: Antibody responses were more promising when used in combination (AUC of 0.80), when all seven antibodies were combined. When anti-"Kit 1"-IgA levels were combined with five host cytokine biomarkers, the AUC increased to 97% (92–100%) with a sensitivity of 95% (95% CI, 73–100%), and specificity of 88.5% (95% CI, 68.7–97%) achieved after leave-one-out cross validation. Conclusion: When used in combination, IgA titres measured with ELISA against multiple Mycobacterium tuberculosis antigens may be useful in the diagnosis of TB. However, diagnostic accuracy may be improved if the antibodies are used in combination with cytokines. Highlights: Antibody-based TB tests are known to be highly specific whereas host cytokine responses have been shown to be sensitive. An approach involving the combination of anti-MTB antibodies and cytokines was assessed as a tool for TB diagnosis. Antibodies alone were promising but diagnostic accuracy increased when they were used in combination with cytokines. Combining antibodies with up to five host inflammatory biomarkers may be a useful approach for the diagnosis of TB.